TINDAKAN SITA JAMIN UNTUK MENJAMIN PELAKSANAAN PUTUSAN DIKEMUDIAN HARI PADA PERKARA PERDATA - Yuliska, Edwin (Fakultas Hukum Universitas Tamansiswa Padang, 2022)
Security confiscation is carried out on the orders of the Judge/Chairman of the Panel before or during the examination process and for the confiscation the Judge/Chairman of the Panel makes a letter of determination. The confiscation is carried out by the Registrar of the District Court / Bailiff with two court officials as witnesses. There are two types of security confiscations, namely security confiscations against the defendant's property (conservatoir beslag) and security confiscations against the plaintiff's property (revindicatoir beslag) (Article 227, 226 HIR. Article 261, 260 RBg.). However, if the confiscation of the guarantee has been carried out and then peace is reached between the two parties to the litigation, then the confiscation of guarantee must be lifted